Sol-gel template synthesis of visible photoactive Cu-S co-doped mesoporous TiO2 catalyst - Hamisu, Abubakar; Bala, Sani Saminu; Bello, Abdu Muhammad; Abubakar, Abdullahi Musa; Adeyi, Abel Adekanmi (Taylor & Francis Ltd, 2023)
A new visible photoactive catalyst (Cu, S/PEG-PVA/TiO2) was synthesized by the sol-gel method. In addition, Cu, S/TiO2 and Bare TiO2 were synthesized to compare their properties and activities. The synthesized catalysts were characterized using XRD, N-2 adsorption-desorption measurements, SEM, TEM, EDX, UV-Vis spectroscopy and TGA. The photocatalytic activities of the synthesized photocatalysts were evaluated by measuring the photocatalytic degradation of 4-nitrophenol under visible light irradiation. Then, the impacts of three parameters, (catalyst loading, pH and H2O2 concentration) for optimization and modelization of the 4-nitrophenol photodegradation were studied using the response surface methodology. Optimal conditions obtained from statistical analysis at a catalyst loading of 1 gL(-1), pH of 3.98 and H2O2 concentration of 8 mg/L have shown the highest 4-NP percentage degradation of 70.5% in 1 h. The results predicted by the models were found to be in good agreement with those obtained by performing the experiment (R-2 = 0.9443 and Adj-R-2 = 0.9038).
Keywords: Sol-gel; Bi-template; Cu-S codoped; mesoporous TiO2; RSM